Estimation of the adult population at high risk of developing lung cancer in the European Union. (December 2018) - González-Marrón, Adrián; Martín-Sánchez, Juan Carlos; Matilla-Santander, Nuria; Cartanyà-Hueso, Àurea; Lidón-Moyano, Cristina; Vidal, Carmen; García, Montse; Martínez-Sánchez, Jose M.
Highlights: Between 17 and 34 million citizens in the EU are at high risk of lung cancer. Between 10 and 25% of smokers in the EU are at high risk of lung cancer. The proportion of former smokers at high risk is not negligible. In most countries, the proportion of men at high risk is higher than in women. Abstract: Background Lung cancer mortality accounts for over 266, 000 deaths in the European Union (EU) every year, most of them attributed to smoking. The aim of this study was to estimate the prevalence of the adult population at high risk of developing lung cancer in the EU in 2014. Methods This is a cross-sectional study. We used data from the Special Eurobarometer 429 (n = 27, 801). The fieldwork was conducted between November-December 2014. High risk of lung cancer was defined using the criteria of the National Lung Screening Trial (NLST) and the Dutch-Belgian Lung Cancer Screening Trial (NELSON). Results One out of ten smokers (11.6% of men and 9.6% of women) according to NLST criteria and one out of four smokers (24.6% of men and 22.4% of women) according to NELSON criteria are currently at high risk of lung cancer in the EU. According to both criteria, the prevalence of former smokers at high risk of lung cancer is under 10%. Conclusion Around 17 million citizens in the EU according to NLST criteria and 34 million according to NELSON criteria (around 4% and 8% of the adult population, respectively) are at high risk of developing lung cancer. Since the implementation of lung cancer screening programs still remains controversial, primary prevention activities should be encouraged.